Hirschsprung Disease in Jordan: A Review and Status Update: Hirschsprung Disease in Jordan - Alkhateeb, Asem; Shahatit, Shadi (Jordan Medical Journal, 2024)
Hirschsprung disease (HSCR) is a congenital disorder characterized by the absence of neuronal ganglions in the intestine, leading to impaired bowel movement and serious constipation. It affects 1 in 5,000 live births. HSCR can be syndromic or non-syndromic and the genetics behind it is complex as many genes are implicated with its etiology and prognosis, most importantly, the RET gene. HSCR is diagnosed from colon biopsies, but novel molecular testing of many gene panels is promising. Furthermore, HSCR prevalence across English, Hispanic, African American, Asian, or Arabian populations have been investigated, and the alleles frequencies of RET ClinVar entries provided. In this review, we aim to discuss the status of the disorder in Jordan. Seven publications were summarized and sub-grouped into: (1) case reports, (2) mortality rates, and (3) genetic testing. Also, information was gathered from Jordanian families with HSCR children about health and social aspects in Jordan. The research in Jordan is modest and demands further investigation on the molecular basis of the diseases within the Jordanian population so that optimal management can be expected and awareness raised for this rare disease in the society.